Gram Negative Bacteria Isolated from Blood Cultures and Their Antibiotic Susceptibility - Metekoray Vural; Mehtap Hülya Aslan (Trends in Surgical Sciences)
Objective: Blood stream infections cause serious mortality and morbidity in patients, especially in intensive care units of hospitals. Detection of the causative microorganism as soon as possible and planning appropriate antibiotic treatment reduce mortality rates. The aim of this study is to determinethe gram negative bacteria grown in blood culture samples brought to the laboratory from various services, primarily surgical intensive care units of our hospital, and the antibiotics effective on them, and to contribute to clinicians initiating empirical treatment.Methods: Gram negative bacteria grown in blood culture samples brought to the laboratory from various services, primarily surgical intensive care units of our hospital, and the antibiotics effective on them were investigated retrospectively. Results: Gram negative bacteria were grown in 332 (23%) of 1,270 samples with blood culture growth. The growth rate in blood culture samples sent from intensive care units was in the first place with 165 (49%). Of the isolated gram negative bacteria, 113 (34%) were Acinetobacter Baumannii, 58 (17%) were Escherichia coli, 51 (15%) were Klebsiella pneumoniae, 42 (12%) were Pseudomonas aeruginosa, 16 (4%) were Brucella spp., 14 (4%) were Enterobacterspp., 12 (3%) were Serratia marcescens, 12 (3%) were Burkholderia cepacia, 10 (3%) were Stenotrophomonas maltophilia, and 4 (1%) were Citrobacter spp. Extended spectrum beta-lactamase (ESBL) was detected in 37 (80%) of K. Pneumonai strains and 28 (48%) of E. Coli strains.Conclusion: In order to reduce the mortality and morbidi ty rates of patients hospitalized in intensive care units, laboratories performing blood culture should conduc tmore comprehensive studies to identify the agents they isolate and the appropriate antibiotics to guide clinicians in initiating treatment.